Stealing time: migration, temporalities and state violence - Bhatia, Monish; Canning, Victoria (Palgrave Macmillan, 2021)
This book draws together empirical contributions which focus on conceptualising the lived realities of time and temporality in migrant lives and journeys. This book uncovers the ways in which human existence is often overshadowed by legislative interpretations of legal and illegalised. It unearths the consequences of uncertainty and unknowing for people whose futures often lay in the hands of states, smugglers, traffickers and employers that pay little attention to the significance of individuals time and thus, by default, their very human existence. Overall, the collection draws perspectives from several disciplines and locations to advance knowledge on how temporal exclusion relates to social and personal processes of exclusion. It begins by conceptualising what we understand by time and looks at how temporality and lived realities of time combine for people during and after processes of migration. As the book develops, focus is trained on temporality and survival during encampment, border transgression, everyday borders and hostility, detention, deportation and the temporal impacts of border deaths. This book both conceptualises and realises the lived experiences of time with regard to those who are afforded minimal autonomy over their own time: people living in and between borders